Growth patterns of breast fed and formula fed infants in the first 12 months of life: an Italian study. Issue 5 (1st November 1999) - Agostoni, C; Grandi, F; Giannì, M L; Silano, M; Torcoletti, M; Giovannini, M; Riva, E
Abstract : AIM: To compare the growth patterns of breast fed and formula fed Italian infants in the first 12 months of life using World Health Organisation (WHO) reference data. METHODS: The growth patterns of 73 breast fed infants (36 male, 37 female) and 65 formula fed infants (35 male, 30 female) were compared. Solid foods were introduced with the same weaning schedules from the 5th month in both groups. The weight for age (WA), length for age (LA), and weight for length (WL) z scores (National Center for Health Statistics–WHO data) were calculated at birth, 1, 2, 3, 4, 6, 9, and 12 months. RESULTS: Breast fed infants had the highest z scores (WA, WL) at birth. Breast fed groups had significantly higher growth indices at 1 month (WA, LA), 2 months (WA) and 3 months (WA, LA) of age. Compared to breast fed groups, formula fed infants showed significantly higher WA z score changes in the 1–2, 2–3, 3–4, and 4–6 month intervals. LA z score changes were higher for breast fed infants at 0–1 month and for the formula fed infants at 4–6 months. In the 6–12 month interval growth indices progressively increased for the formula fed infants and declined for infants breast fed for longer (12 months). The 0–12 month changes in WA, LA, and WL z scores were positive for formula fed infants and negative for the 12 month breast fed group. Nevertheless, the 12 month breast fed group showed an absolute WA z score just below 0 (mean (SEM) −0.04 (0.26)) at 12 months. CONCLUSION: The growth pattern of breast fed and formula fed Italian infants differs in the first 12 months of life. This questions the validity of current reference values for monitoring the growth of breast fed infants. Growth indices in breast fed groups, high at birth and closer than expected to the reference at 12 months, may reflect differences in genetic factors, intrauterine conditions, or both.